(untitled) (Ideal Journal of Multidisciplinary Research, 2026)
This article examines the process of developing analytical competence among early childhood educators as a holistic system comprising operational, reflective, and value-based components. It argues for the necessity of a phased approach to developing this competence using complementary pedagogical methods. The case method and portfolio are analyzed as the primary means of developing the operational component, as they ensure the connection between theoretical knowledge and practical activity and the development of skills for analyzing professional situations. The development of the reflective component is examined through a SWOT analysis to evaluate one’s own pedagogical practice critically. The formation of the value component is linked to the use of group discussion methods aimed at understanding professional values and exchanging experiences. The structure of the integrative method is presented, including the stages of analysis, interpretation, evaluation, and collective reflection on pedagogical practice. It is concluded that the comprehensive application of these methods contributes to increasing the effectiveness of teachers’ professional activities in the context of modern preschool education.